Improving learning through classroom experience in Tanzania - Pattni, Ravina; Villavicencio Peralta, Xuzel; Toyinbo, Oluyemi; Proctor, Jamie; Forbes, Catriona; Atherton, Paul; Haßler, Björn (Laterite, Fab Inc, Open Development & Education, 2023)
This conference paper was delivered at UKFIET 2023 (Oxford). IT was a joint presentation between Laterite, Fab Inc, and Open Development & Education, as well as FCDO.
Keywords: _r:AddedByMyEducationEvidence